Comprehensive analysis of paddy seeds for designing of precision planters - guru, prabhat kumar; Shrivastava, Atul Kumar; Tiwari, Priyanka; Khandai, Suryakant; Nagori, Ankur; Naik, Rajesh Kumar (ORYZA-An International Journal of Rice, 2024)
Rice is a staple food for a major global population, and increasing rice production is crucial for addressing food security challenges. Precision planters have the potential to enhance rice productivity and input use efficiency. However, designing precision planters requires a comprehensive understanding of the physical and engineering properties of paddy seeds. This research paper aims to generate a database of these properties to aid in the design of precision planters. The study examined three popularly grown rice varieties (IR 64, JR 206, and Kranti) in terms of their physical and engineering properties. The seeds were analyzed at different stages, including the dry stage, 24 hours soaking and 48 hours of soaking. The results shows design values of metering unit with maximum grain dimensions (10.20 mm length, 3.39 mm breadth, 2.68 mm thickness), equivalent diameter 4.336 mm, sphericity 0.456, average friction coefficient 0.48, and maximum apparent volume 9.7 cm3. Based on the results design values for metering mechanism is calculated which is very much essential for designing of precision seeder for rice.